1997
DOI: 10.1103/physrevb.55.11702
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic flux instabilities in superconducting niobium rings: Tuning the avalanche behavior

Abstract: We study the dynamics of superconducting vortices in Nb rings as the system is continuously driven to the depinning threshold by the slow ramping of an external magnetic field. Miniature Hall probes simultaneously detect local and global flux changes arising from vortex motion. With decreasing temperature, the dynamics evolve continuously from smooth flow to several types of avalanche behavior. In particular, we observe a crossover from broad to narrow size distributions of avalanche events which correspond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
59
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 23 publications
3
59
0
Order By: Relevance
“…In addition, recent magnetic studies in Nb films [14,15] reported the existence of a structure that reminisces of the second magnetization peak (SMP) which is usually observed in high-T c superconductors [16,17,18,19,20]. These studies concluded that for the case of Nb films the "second magnetization peak" ("SMP") is motivated by thermomagnetic insta- ‡ Corresponding author (densta@ims.demokritos.gr) bilities (TMI) that occur in the low-temperature regime, far below the upper-critical field [14,15,21]. Despite the need for the complete theoretical understanding of the underlying mechanism that motivates the "SMP", the existence of the accompanying TMI should be studied experimentally in more detail, because the undesirable flux jumps constitute a serious limitation for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent magnetic studies in Nb films [14,15] reported the existence of a structure that reminisces of the second magnetization peak (SMP) which is usually observed in high-T c superconductors [16,17,18,19,20]. These studies concluded that for the case of Nb films the "second magnetization peak" ("SMP") is motivated by thermomagnetic insta- ‡ Corresponding author (densta@ims.demokritos.gr) bilities (TMI) that occur in the low-temperature regime, far below the upper-critical field [14,15,21]. Despite the need for the complete theoretical understanding of the underlying mechanism that motivates the "SMP", the existence of the accompanying TMI should be studied experimentally in more detail, because the undesirable flux jumps constitute a serious limitation for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Different scenarios are considered resulting in a variety of flux patterns, e.g., magnetic turbulence [8,9], kinetic flux front roughening [10], magnetic micro avalanches [11,12], flux dendrites [13,14,15,16,17], thermomagnetic fingering [18], bending of flux-antiflux interface [19,20], and flux front corrugation [21].…”
mentioning
confidence: 99%
“…For a magnetic field oriented perpendicular to the Nb film surface such vortex motion leads to flux jumps [8,9]. These flux jumps were interpreted as a thermomagnetic instability of the critical state.…”
Section: Introductionmentioning
confidence: 99%